2011
DOI: 10.1542/peds.2010-3304
|View full text |Cite
|
Sign up to set email alerts
|

Media Use and Child Sleep: The Impact of Content, Timing, and Environment

Abstract: WHAT'S KNOWN ON THIS SUBJECT:Media use has been shown to negatively affect child sleep, especially in the context of evening use or with a television in the child's bedroom. WHAT THIS STUDY ADDS:Increased sleep problems were observed in preschool-aged children for each additional hour of daytime violent media content or evening media use. No such effect was observed with nonviolent daytime use. abstract BACKGROUND: Media use has been shown to negatively affect a child's sleep, especially in the context of even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
144
2
14

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(183 citation statements)
references
References 29 publications
(30 reference statements)
14
144
2
14
Order By: Relevance
“…61 An additional limitation of the current study is that we were unable to accurately assess the timing of screen-based media use. As a result, although we suspect that much of the reductions in total sleep time in the current study are related to nighttime (versus daytime) media use, similar to previous research, 62 we cannot definitively say that this is the case. Therefore, future studies in individuals with ASD or ADHD should include measures that better approximate prebedtime media exposure.…”
Section: Figuresupporting
confidence: 43%
“…61 An additional limitation of the current study is that we were unable to accurately assess the timing of screen-based media use. As a result, although we suspect that much of the reductions in total sleep time in the current study are related to nighttime (versus daytime) media use, similar to previous research, 62 we cannot definitively say that this is the case. Therefore, future studies in individuals with ASD or ADHD should include measures that better approximate prebedtime media exposure.…”
Section: Figuresupporting
confidence: 43%
“…In our previous article describing the relationship between media use and child sleep at baseline in this study, we found not only that evening media use was associated with increased sleep problems but so was violent media use earlier in the day. 2 If the intervention affected child sleep by reducing violent media consumption across the day, the effects may have been mediated by decreases in factors such as fears and state anxiety, 20 arousal state at bedtime, or hyperactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Although this finding has been consistently replicated with high levels of use, bedtime use, and violent or frightening media content, [1][2][3][4][5][6][7] effects have been observed across cultures and in all media formats (television, 6,[8][9][10] video games, [10][11][12] and computers 11,13,14 ) and across the age spectrum, including preschoolers, 2,7-9 school-aged children, 1,[3][4][5][6] and adolescents and adults. [13][14][15] Much of the existing research linking media use to child sleep problems has been crosssectional, however, raising the possibility that the causality is reversed; that is, that sleep problems are leading to increased media use, evening media use, and exposure to violent media content, rather than the other way around.…”
mentioning
confidence: 97%
“…17 The American Academy of Pediatrics' recommendations to limit screen time are more than a decade old, but there has been limited success in reducing children' s TVV. 17 Understanding modifiable factors that contribute to TVV among youth is essential because excessive time spent viewing television is associated with unfavorable health and social outcomes in children and adolescents, including obesity, [18][19][20] poor sleep, 21 physical inactivity, 22 and poor academic achievement. 23 In the current study, we examined the effect of parental TVV on child TVV compared with household and bedroom television access, parental rules, and demographic variables in national parent samples.…”
mentioning
confidence: 99%